2014
DOI: 10.1111/jvh.12226
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic immune biomarker changes during interferon/ribavirin treatment in HIV/HCV co‐infected patients

Abstract: Chronic viral infections lead to persistent immune activation, which is alleviated by eradicating or suppressing the infection. To understand the effects of interferon treatment on immune system activation by chronic infections, we evaluated kinetic patterns of a broad spectrum of serum biomarkers during HCV treatment in HIV/HCV co-infected patients. HCV viral load and 50 biomarkers were analyzed at baseline and 27 time points during pegylated interferon and ribavirin (IFN/RBV) treatment of 12 HIV/HCV co-infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…Although dysregulated myelopoiesis by inflammatory cytokines, such as IL‐6, IL‐10, TGF‐ β and prostaglandin E 2 that are up‐regulated during chronic HCV infection, may partially explain the expansion of MDSCs, the molecular nature of this process is unclear. Previous studies have shown that increased expression of arginase 1, nitric oxide synthase or reactive oxygen species is the primary mechanism by which MDSCs promote immunosuppression during chronic HCV infection .…”
Section: Discussionmentioning
confidence: 99%
“…Although dysregulated myelopoiesis by inflammatory cytokines, such as IL‐6, IL‐10, TGF‐ β and prostaglandin E 2 that are up‐regulated during chronic HCV infection, may partially explain the expansion of MDSCs, the molecular nature of this process is unclear. Previous studies have shown that increased expression of arginase 1, nitric oxide synthase or reactive oxygen species is the primary mechanism by which MDSCs promote immunosuppression during chronic HCV infection .…”
Section: Discussionmentioning
confidence: 99%
“…Blocking PDGF signaling inhibits HSC proliferation and ameliorates liver fibrogenesis ( 12 ). Clinical studies have additionally confirmed that excessive activation of PDGF and its downstream molecules appears to be associated with the extent of necroinflammation and fibrosis in patients with hepatic damage ( 13 15 ). Therefore, the PDGF signaling pathway serves important roles in the development and prognosis of hepatic fibrosis.…”
Section: Introductionmentioning
confidence: 90%
“…In some studies, IFN-γ was negatively correlated with liver fibrosis [ 33 ], while IFN-γ was also found to have proinflammatory effects that can aggravate disease progression and organ dysfunction [ 30 ], and an increased production of IFN-γ is observed among cirrhotic patients [ 34 ]. Soluble IL-10 was higher in HIV–HCV-coinfected patients than in HIV-negative persons [ 27 ], but could be reduced following peg-interferon plus ribavirin (PR) treatment for HCV [ 35 ]. GM-CSF was higher in HIV patients than in healthy control subjects [ 31 ], and may promote liver damage and liver fibrosis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%